DEVELOPMENT OF BUSINESS MATHEMATICS COUNTING INTEGRATION METHODS IN THE BIG DATA ERA IN FOOD BARN MANAGEMENT - Etika Sabariah Tika; Agung Suprianto; Isron Isron (SEAN Institute, 2022)
The post-pandemic economic crisis created a journey of ups and downs in business, business and work in the aggregate and individually. The problems faced in agriculture and plantations are: inflation, famine. and post-harvest situations that leave farmers disillusioned. The aim of the research is to develop a solution synergy in the integration space in the business mathematics space. Applied research on experimental tests was carried out using simulated data. This method injects theory into the case through the moving average method and simple comparisons. The results of the analysis are in the form of the first rhetoric given to farmers to answer the problem that the selling price of crops cannot cover agricultural production through 1) the application of a moving average as a sales target that adjusts information on market conditions owned by the local KUD, for farmers of crop yields with a longer expiry date to determine an open and close selling system in an effort to maintain a balanced price between the wishes of farmers and the desires of consumers. Meanwhile for fruit and vegetable farmers, moving averages are used to determine sales targets, not to implement an open and close system because the fruit and vegetable expiration period is faster, but to direct farmers to make decisions to expand the market through simple comparisons in market space, as well as product innovation. The next analysis is the rhetoric for KUD which is a food storage data center that is connected by the government and stakeholders to help farmers remain productive. Meanwhile for fruit and vegetable farmers, moving averages are used to determine sales targets, not to implement an open and close system because the fruit and vegetable expiration period is faster, but to direct farmers to make decisions to expand the market through simple comparisons in market space, as well as product innovation. The next analysis is the rhetoric for KUD which is a food storage data center that is connected by the government and stakeholders to help farmers remain productive. Meanwhile for fruit and vegetable farmers, moving averages are used to determine sales targets, not to implement an open and close system because the fruit and vegetable expiration period is faster, but to direct farmers to make decisions to expand the market through simple comparisons in market space, as well as product innovation. The next analysis is the rhetoric for KUD which is a food storage data center that is connected by the government and stakeholders to help farmers remain productive..